Exploring the Impact of Artificial Intelligence on Drug Discovery and Biomedical Research in Zoology: An Experimental Investigation - Bera, Anirban; Banerjee, Kaushik; Adhikary, Sudipta (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The integration of Artificial Intelligence (AI) into zoological science is revolutionizing drug discovery and biomedical applications. AI-driven methods improve the efficiency and accuracy of finding potential therapeutic compounds, significantly cutting down the time and cost traditionally associated with drug development. Using machine learning algorithms and large datasets, AI can predict the biological activity, toxicity, and efficacy of new drugs, streamlining the preclinical testing phase. Artificial Intelligence (AI) is used in zoological science to help researchers better comprehend animal models and complicated biological processes, which are important in biomedical research. In behavioral research, genetic sequencing, and picture analysis, sophisticated artificial intelligence techniques can identify minute patterns and connections that a human could overlook. These tools help researchers understand complex biological processes and disease mechanisms, which paves the way for more specialized and efficient medical interventions. AI is crucial to personalized medicine because it helps customize care based on patient genetic profiles and medical records. Better patient care is promoted by this individualized strategy, which minimizes side effects and enhances treatment outcomes. While AI's potential in drug discovery and biomedical applications is immense, there are challenges in its implementation. Issues such as data privacy, the need for high-quality and large datasets, and the complexity of integrating AI systems into existing research frameworks can pose significant hurdles. Additionally, ethical considerations and the need for regulatory oversight are crucial in ensuring the responsible use of AI in these fields. The developments in biomedical applications and AI-driven drug discovery point to a bright future where interdisciplinary cooperation and technological innovation will enhance zoological science. In the end, this integration improves our capacity to handle urgent health issues and speeds up scientific discovery, which improves health and wellbeing worldwide.